Oxygen in Red Blood Cell Concentrates: Influence of Donors’ Characteristics and Blood Processing - Bardyn, Manon; Martin, Agathe; Dögnitz, Nora; Abonnenc, Mélanie; Dunham, Andrew; Yoshida, Tatsuro; Prudent, Michel (Frontiers in Physiology, 2020)
Objective: Unexpectedly wide distribution (<5 to >95%) of hemoglobin oxygen saturation (sO2) within red cell concentrates (RCCs) has recently been observed. Causes of such variability are not yet completely explained whereas the role of oxygen and oxidative lesions during storage of RCCs are known. The objectives of the present study are to characterize sO2 distribution in RCCs produced in a Swiss blood center and to investigate the influence of processing and donors’ characteristics. Methods: sO2 was measured in 1701 leucocyte-depleted RCCs derived from whole blood donations in both top-bottom (TB; component filtered, SAGM) and top-top (TT; whole blood filtration, PAGGSM) RCCs. sO2 was measured non-invasively through the PVC bag prior to storage by resonance Raman spectroscopy. Gender, age, blood type, hemoglobin level and living altitude of donors, as well as process method and time-to-process were recorded. Results: Overall, the sO2 exhibited a wide non-Gaussian distribution with a mean of 51.2±18.5%. Use of top-top kits resulted in a 16% higher sO2 (P <0.0001) than with top-bottom ones. Waiting time before processing had only modest impact, but the blood processing itself reduced the sO2 by almost 12% (P <0.0001). sO2 was also significantly affected by some donors’ characteristics. RCCs from men exhibited 25% higher sO2 (P <0.0001) than those donated by women. Multivariate analysis revealed that the apparent correlation observed with hemoglobin level and age was actually due to multicollinearity with the sex variable. Finally, we noticed no significant differences across blood type but found that altitude of residence was associated with the sO2 (i.e. higher in higher living place). Conclusion: These data confirm wide sO2 distribution in RCCs reported recently. The sO2 was impacted by the processing and also by donors’ characteristics such as the gender and the living altitude, but not by the hemoglobin level, blood group and donor age. This study provides new hints on the factors influencing RBCs storage lesions, since they are known to be related to O2 content within RCCs, giving clues to better process and to better store RBCs and therefore improve efficacy of transfusion.